2015
DOI: 10.1111/jdi.12437
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating level of a cytokine, pancreatic‐derived factor, is associated with metabolic syndrome components in a Chinese population

Abstract: Aims/IntroductionPancreatic‐derived factor (PANDER) is an important factor involved in obesity, glucose intolerance and abnormal lipid metabolism in animals. Nevertheless, the relationship between PANDER and metabolic syndrome (MetS) in humans has not yet been reported.Materials and MethodsTo determinate the relationship between PANDER and MetS components, 212 individuals aged between 40 and 65 years were recruited. Fasting plasma PANDER and other variables were measured. Correlations of plasma PANDER and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…During preparation of this manuscript, the first report examining circulating PANDER is currently in-press and measured these levels in an Asian population (n=212, aged 40–65) with varying degrees of glucose intolerance and T2D (Cao, Yang, Lai et al, 2015). Cao et al revealed systemic PANDER levels are significantly correlated with increased fasting blood glucose (FBG), triglycerides, and high-density lipoprotein cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During preparation of this manuscript, the first report examining circulating PANDER is currently in-press and measured these levels in an Asian population (n=212, aged 40–65) with varying degrees of glucose intolerance and T2D (Cao, Yang, Lai et al, 2015). Cao et al revealed systemic PANDER levels are significantly correlated with increased fasting blood glucose (FBG), triglycerides, and high-density lipoprotein cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Encompassing prior PANDER research, an emerging hypothesis suggests that the pathophysiological conditions of T2D could potentially induce increased circulating PANDER levels contributing to selective hepatic insulin resistance (SHIR) resulting in increased hepatic glucose output and lipogenesis (Wilson, Robert-Cooperman and Burkhardt, 2011, Wang, Burkhardt, Guan et al, 2012), as precisely observed in our PANTG model. Recent evidence has now indicated that circulating PANDER levels are elevated and associated with metabolic syndrome components in a Chinese population (Cao, Yang, Lai et al, 2015). Plasma PANDER levels significantly correlated with fasting plasma glucose, 2 hour plasma glucose, and triglyceride levels.…”
Section: Introductionmentioning
confidence: 99%
“…It is probably because FAM3B, both full‐length and recombinant, can also induce islet β‐cell apoptosis by upregulating caspase‐3. Coincidentally, a cross‐sectional study has proved that FAM3B is negatively associated with FINS in humans. Furthermore, compared with new‐onset diabetes and healthy controls, circulating FAM3B levels are significantly increased in individuals with long‐standing diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Overall, these clinical and experimental studies had established that PANDER plays important roles in the regulation of glucose and lipid metabolism. [17][18][19][20] In the previous study, 13 we demonstrated that PANDER promotes the lipogenesis in hepatocytes by inhibiting Akt to activate FOXO1. However, whether PANDER activates FOXO1 activity via other mechanism(s) beyond Akt repression remains unknown.…”
Section: Introductionmentioning
confidence: 97%